Refusal of Representation in Advance Care Planning: A Case-Inspired Ethical Analysis - Peters, Andrew T. (The Hastings Center report, 2023)
Unrepresented patients—people without capacity to make medical decisions who also lack a surrogate decision-maker—form a large and vulnerable population within the United States health care system. The burden of unrepresentedness has rightly prompted widespread calls for more and better advance care planning, in which still-healthy patients are encouraged to designate a surrogate decision-maker and thus avoid the risk of becoming unrepresented. However, we observe that some patients, even with available social contacts and access to adequate advance care planning services, simply decline to name a surrogate decision-maker. We propose a novel concept of “informed refusal of representation” (“IRR”) to characterize the position held by some such patients, who are often overlooked in prior work on unrepresentedness. We then discuss physicians’ ethical obligations in the face of such a refusal and avenues by which physicians can support patients without surrogates in receiving goal-concordant care.